Trends in Lactose-Derived Bioactives: Synthesis and Purification - Vera-Vera, C (Springer, 2022)
Lactose obtained from cheese whey is a low value commodity despite its great potential as raw material for the production of bioactive compounds. Among them, prebiotics stand out as valuable ingredients to be added to food matrices to build up functional foods, which currently represent the most active sector within the food industry. Functional foods market has been growing steadily in the recent decades along with the increasing awareness of the World population about healthy nutrition, and this is having a strong impact on lactose-derived bioactives. Most of them are produced by enzyme biocatalysis because of molecular precision and environmental sustainability considerations. The current status and outlook of the production of lactose-derived bioactive compounds is presented with special emphasis on downstream operations which are critical because of the rather modest lactose conversion and product yields that are attainable. Even though some of these products have already an established market, there are still several challenges referring to the need of developing better catalysts and more cost-effective downstream operations for delivering high quality products at affordable prices. This technological push is expected to broaden the spectrum of lactose-derived bioactive compounds to be produced at industrial scale in the near future. Graphical abstract: [Figure not available: see fulltext.]. © 2021, Jiangnan University.